STANDARISASI MUTU INTERNAL PENELITIAN SETELAH PERGURUAN TINGGI MELAKSANAKAN MELAKUKAN PENGABDIAN MASYARAKAT - Anita Ariani; Syahrani Syahrani (CV. ADIBA AISHA AMIRA, 2021)
Research to the community is a source of knowledge, so it can provide guidelines for solving problems, and getting answers and obtaining solutions. So that scientists will gain insight, knowledge and new ways of thinking about the problems being researched and community service is the criteria for the mechanism for implementing community service activities. and Community service is an activity of the academic community in the form of utilizing science and technology in order to advance the welfare of the community and educate the nation's life. And Education is an activity of delivering Science, Technology and Arts (IPTEK); Research is an activity of discovery, creation and development. Education is an activity of delivering Science, Technology and the Arts (IPTEK). Community service is the implementation of the practice of science, technology and cultural arts directly in the community institutionally and as a dissemination of the Tridharma of higher education and noble responsibilities in an effort to develop community capabilities, so as to accelerate the growth rate of achieving national development goals. Community service as one of the Tridarma of higher education which occupies a strategic position in fostering and educating the community to improve the quality of life of the community in the activities of the academic community in the form of utilizing science in order to advance the welfare of the community and educate the nation's life. Referring to the Tridharma of higher education which includes education, research and community service to the community, universities should be able to carry out these dharmas in an integrated functional manner. The first is community development in the field of science by establishing a library in the middle of the village as the center or center of this service, secondly structuring and improving the agricultural environment by providing integrated agricultural system counseling, especially to farmers, and thirdly strengthening financially in the economic field by building business skills with various trainings. , balanced with assistance to the community. This program aims to create a society that is rich in knowledge, a society that is strong in the financial and economic sector and a society that cares about the surrounding environment.